2020
DOI: 10.1186/s12959-020-00245-8
|View full text |Cite
|
Sign up to set email alerts
|

Combined thrombogenic effects of vessel injury, pregnancy and procoagulant immune globulin administration in mice

Abstract: Background Pregnant women are at increased risk of thrombotic adverse events. Plasma derived immune globulin (IG) products, which are used in pregnancy for various indications, may contain procoagulant impurity activated coagulation factor XI (FXIa). Procoagulant IG products have been associated with increased thrombogenicity but their effect in pregnancy is unknown. Methods Late pregnant (gestation days 17–20) or early lactation (days 1–3) and control female mice were treated with IGs supplemented with huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…We used pooled plasma to model the average population response, but we lacked information about possible subject-to-subject variability in TG sensitivity, which will need to be obtained in future studies that utilize single donor samples for each species. Our TG results appear consistent with previous studies of individual animal donors [8][9][10][15][16][17][18][19]. Consistent with previous reports [9,17,18], we observed that rat, mouse, and rabbit samples had smaller thrombin signals and lower TPT and clot times than human plasmas.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We used pooled plasma to model the average population response, but we lacked information about possible subject-to-subject variability in TG sensitivity, which will need to be obtained in future studies that utilize single donor samples for each species. Our TG results appear consistent with previous studies of individual animal donors [8][9][10][15][16][17][18][19]. Consistent with previous reports [9,17,18], we observed that rat, mouse, and rabbit samples had smaller thrombin signals and lower TPT and clot times than human plasmas.…”
Section: Discussionsupporting
confidence: 93%
“…Our study may assist in the preclinical evaluation of these inhibitors in animal species. To our knowledge, only two studies have previously observed TG triggered by FXIa in the plasma of animals, and both were performed in mice [ 16 , 35 ]. In the present study, we obtained results analogous to the study [ 16 ] in murine plasma, and we added a comparison to other species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased lumen area of placental arteries and artery wall thickening occur in SARS-CoV-2-positive women independent of symptoms. The overlap of vessel wall abnormalities, blood flow abnormalities, and hypercoagulable state increases the risk of thrombosis while gradually diminishing placental functions (Khalil and Granger, 2002;Xu et al, 2020). SARS-CoV-2 damages the placenta by inducing inflammation in the villous chamber (Bouachba et al, 2021).…”
Section: Changes In Placenta Caused By Sars-cov-2 Infectionmentioning
confidence: 99%
“…Normal pregnancy is a hypercoagulable state [1,2] with a balance between coagulation and fibrinolysis, promoting pro-coagulation and limiting fibrinolysis. Pregnancy encourages thrombosis with a reduction of hemorrhagic risk, particularly during the third trimester.…”
Section: Introductionmentioning
confidence: 99%